Author Correction: Pupil size reflects successful encoding and recall of memory in humans - Kucewicz, Michal T; Dolezal, Jaromir; Kremen, Vaclav; Berry, Brent M; Miller, Laura R; Magee, Abigail L; Fabian, Vratislav; Worrell, Gregory A (Scientific reports, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.